P217 Volatile organic metabolites to predict clinical response to biological therapy in inflammatory bowel disease. (30th January 2023) - Ribaldone, D G; Arezzo, A; Cardenia, V; Caviglia, G P; Abate, M L; Saracco, G M; Astegiano, M; Morino, M
Abstract: Background: Volatiles organic metabolites (VOMs) are a large group of carbon-bound chemicals elements, gaseous at room temperature that are the products of metabolism. There is increasing evidence that variations in faecal VOMs indicate gastroenterological diseases. No study assessed VOMs in the setting of predicting therapeutic response in inflammatory bowel disease (IBD). Methods: We conducted a prospective study in which we consecutively recruited IBD patients with indications for treatment with biologics. The primary outcome of our study was the evaluation of prediction ability of VOMs of clinical response at 12 months of adalimumab or vedolizumab therapy. Secondary outcomes included correlations of VOM with clinical features of IBD. Results: We recruited 50 patients with IBD whose stools were analysed with gold standard technique mass spectrometer (MS) / gas chromatography (GC). Thirty-one patients were treated with adalimumab (of which 30 Crohn's disease, and 1 ulcerative colitis, UC), 19 patients with vedolizumab (of which 12 CD and 7 UC). VOMs were not influenced by age, disease duration, sex, smoking habit. Two VOMs, octenol and, in particular, methyl indole were able to distinguish ulcerative colitis (UC) from Crohn's disease (CD) (AUC = 0.72 and 0.85, respectively) and correlate with higher inflammation markers (C-reactive protein, CRP and calprotectin, respectively). Methylbutanal, instead, was a marker of CD and, in particular, of ileal location (p = 0.01). These results were confirmed at principal component analysis (PCA). Lower levels of ethanol and methyl butanoate correlated with disease remission. Methyl butanoate was able to distinguish remission from active clinical disease, with an accuracy at least equal to that of calprotectin (AUC = 0.69 and AUC = 0.62, respectively). We furthermore demonstrated pre-biologics methyl butyrate prediction ability of clinical response after 12 months of therapy (AUC = 0.68, 95%CI = 0.53-0.81, p = 0.02). Lower levels of methyl indole or of octenol or higher levels of indole were able to predict calprotectin <250 mg/kg without steroid at month 12; undetectable levels of basal ethyl butanoate correlated with calprotectin <250 mg/kg without steroid at month 12 (p = 0.04) in the subgroup of patients treated with vedolizumab, while higher levels of ethyl butanoate correlate with higher CRP levels. Our finding of a lower piperidone level in patients undergoing previous bowel resection is consistent with literature data that found an association between active CD and higher piperidone levels. Conclusion: The characterization of the intestinal metabolome, using VOMs technology, seems to be a promising method for better characterizing IBD and better speculating on their etiopathogenesis.